2018
DOI: 10.1002/cam4.1733
|View full text |Cite
|
Sign up to set email alerts
|

Core‐binding factor acute myeloid leukemia with t(8;21): Risk factors and a novel scoring system (I‐CBFit)

Abstract: BackgroundAlthough the prognosis of core‐binding factor (CBF) acute myeloid leukemia (AML) is better than other subtypes of AML, 30% of patients still relapse and may require allogeneic hematopoietic cell transplantation (alloHCT). However, there is no validated widely accepted scoring system to predict patient subsets with higher risk of relapse.MethodsEleven centers in the US and Europe evaluated 247 patients with t(8;21)(q22;q22).ResultsComplete remission (CR) rate was high (92.7%), yet relapse occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…Sex chromosome loss was reported as a favorable marker for two-year event-free survival (66.9% vs. 43.0%), and in another study showed a modestly favorable, but not significant, effect on disease-free survival (DFS) [103]. Moreover, this last study found that patients with pseudodiploid karyotypes had worse outcome compared with those with hypodiploidy or hyperdiploidy [103]. In contrast, loss of the Y chromosome showed shorter disease-free survival (DFS) for male patients [120].…”
Section: The Genomic Landscape Of Core-binding Factor Acute Myeloid Lmentioning
confidence: 97%
See 3 more Smart Citations
“…Sex chromosome loss was reported as a favorable marker for two-year event-free survival (66.9% vs. 43.0%), and in another study showed a modestly favorable, but not significant, effect on disease-free survival (DFS) [103]. Moreover, this last study found that patients with pseudodiploid karyotypes had worse outcome compared with those with hypodiploidy or hyperdiploidy [103]. In contrast, loss of the Y chromosome showed shorter disease-free survival (DFS) for male patients [120].…”
Section: The Genomic Landscape Of Core-binding Factor Acute Myeloid Lmentioning
confidence: 97%
“…KIT mutations are found in~40% of CBFL with t(8;21) and~33% with inv (16); additionally, an enrichment of exon 17 KIT mutations has been documented in RUNX1-RUNX1T1 patients, and are associated with worse outcome [87,[99][100][101]. Recent large study created an "International CBF group index for t(8;21)" and validated a new risk scoring system, showing that older age, higher WBC index at diagnosis [102], and KIT D816V/Y mutations were risk factors associated with treatment failure (relapse or death) [103]. These studies strongly support the adverse effect of a KIT mutation in the context of CBFL.…”
Section: The Genomic Landscape Of Core-binding Factor Acute Myeloid Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning t(8;21)- and inv(16)-type AMLs, the same large cohort confirms the absence of association with mutations in NPM1 or in the previously cited transcription factor genes, and shows an association between t(8;21) and KIT in 38% of cases. This association has been shown to have poorer outcomes [24]. An even stronger association between inv(16) and NRAS mutations is found in 53% of cases.…”
Section: Distinct Genetic Hierarchies Of Amlsmentioning
confidence: 99%